„Sbigneis” Mikołaja Kotwicza ze Żnina, czyli niedokończone dzieło epickie o prymasie Zbigniewie Oleśnickim - Lewandowski, Ignacy (Studia Europaea Gnesnensia, 2022)
Mikołaj Kotwicz of Żnin (c. 1440–1507) studied law at the Jagiellonian University and probably graduated in Bologna, where he earned a doctor’s degree. Having returned to his country, he was ordained a priest and found employment at the court of Zbigniew Oleśnicki, the Primate of Poland. In Renaissance Italy, where the works of ancient writers drew much scholarly interest, he acquired a wide knowledge of ancient history and literature, as well as mastered Latin and learned poetic art. His command of the latter is evident in his unfinished work “Sbigneis”. It was the only epic poem in medieval Poland, unfortunately made only as an exposition, with the narrative cutting off at the mid point of the hexameter. The poem, modeled on ancient epics such as Greek Iliad by Homer, Roman “Punica” by Silius Italicus, or “Pharsalia” by Lucan, was supposed to narrate a long-standing armed conflict between the related houses of Oleśnicki and Gruszczyński. The idea to embark on such an interesting social issue, albeit touched upon in an exposition only, attests to Kotwicz’s considerable talent and unusual poetic art. The conflict and the composition are clearly outlined; the Latin lan - guage and dactylic hexameter are impeccable. The style of the narrative and the rhetorical figures featured therein are well suited to the epic genre. Only an elaboration of the topic and the ending are missing. The talented author would probably have finished the poem if it had not been for the unfortunate external circumstance following the real-world death of the main character (Zbigniew Oleśnicki), a difficulty that Kotwicz was unable to surmount. Therefore, the epic muse Calliope did not spread her wings in the Polish Middle Ages, even though she was on the right way thanks to a poet from Żnin.